2016
DOI: 10.1097/md.0000000000003806
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Infection Is a Risk Factor for Periprosthetic Joint Infection Among Males After Total Knee Arthroplasty

Abstract: Periprosthetic joint infection (PJI) is a grave complication that can affect patients undergoing total knee arthroplasty (TKA). In this study, we aim to determine whether hepatitis B virus (HBV) infection is a risk factor for PJIs.All patients (1184 males, 3435 females) undergoing primary TKA in Taiwan from 2001 to 2010 were recruited for analysis.The incidence of PJI was 523 among the males with HBV infection and 110 among the males without HBV (per 10,000 person-years, P < 0.001). The males with HBV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Notably, none of the patients developed bleeding complications. Furthermore, no revision surgeries for treatment of wound or periprosthetic joint infection were necessary, although the diagnosis of haemophilia with concomitant hepatitides constitutes a known risk factor and although the infection rate after TAR is documented to be 2%‐8.6% . Only few other studies discussing septic complications after TAR in haemophilic patients can are available for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, none of the patients developed bleeding complications. Furthermore, no revision surgeries for treatment of wound or periprosthetic joint infection were necessary, although the diagnosis of haemophilia with concomitant hepatitides constitutes a known risk factor and although the infection rate after TAR is documented to be 2%‐8.6% . Only few other studies discussing septic complications after TAR in haemophilic patients can are available for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature, we identified only three studies that described outcomes of patients with HBV infection treated with arthroplasty. [12][13][14] Kuo et al 12 reported that HBV infection was a risk factor for periprosthetic joint infection (PJI) following TKAs among men, and Wang et al 13 demonstrated that HBV infection is an independent risk factor for complications of the arthroplasty operation. Kildow et al 14 demonstrated that patients with HBV had increased risk of pneumonia, sepsis, joint infection, and revision surgery at 90 days and two years following arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated a statistically significant increased risk of PJI in patients with a pre-operative confirmation of a genitourinary infection[10,27], nasal S. Aureus and MRSA infections[31], or other distant organ infections[6], such as hepatitis B[44]. …”
Section: Discussionmentioning
confidence: 99%
“…We believe that if a patient is known to have systemic infection, or a localised infection but distant to the operative joint, the risk of haematological spread of infection to the implant is highly likely. We have demonstrated a statistically significant increased risk of PJI in patients with a pre-operative confirmation of a genitourinary infection[ 10 , 27 ], nasal S. Aureus and MRSA infections[ 31 ], or other distant organ infections[ 6 ], such as hepatitis B[ 44 ].…”
Section: Discussionmentioning
confidence: 99%